Contingent Fit-Misfit and Business Unit Performance (A Review Based on the Perspective of the Congruency Hypothesis) - Diana Zuhroh (AFRE (Accounting and Financial Review), 2019)
This study was designed to obtain the influence of contingent fit and misfit on business unit performances in the perspective of the congruency hypothesis. Fit is reached when the company implements a low-cost strategy, practices traditional management accounting and uses automation information technology. Conversely, the company implements differentiation strategy tend to practices strategic management accounting and enabler information technology. This study was a survey method using questionnaires, and regression was used to analyze the data. This study concluded that contingent fit has a positive influence on the performance of customer, internal process, and learning/growth for business units in Fit group. However, the influence of contingent misfit on the performance of financial, customer, internal process and learning/ growth was inconsistent.  According to the Congruency Hypothesis, when the three subsystems are in fit, the configuration to be formed is a straight or almost straight line, which means, the level of elements in subsystems is equal. For these business units, the contingent fit has a positive influence on performance. Conversely, when the three elements are in misfit, the configuration to be formed is not a straight line. This study failed to prove the influence of contingent misfit on the performance of financial, customer, internal process and learning/growth. DOI: https://doi.org/10.26905/afr.v2i1.3170